MO944: Persistent Microscopic Hematuria At Kidney Donor Screening and Long-Term Post-Donation Kidney Outcomes. (3rd May 2022) - Van Der Weijden, Jessica; Van Londen, Marco; Pol, Robert; Sanders, Jan-Stephan; Navis, Gerjan; Nolte, Ilja; De Borst, Martin; Berger, Stefan P
Abstract: BACKGROUND AND AIMS: According to current guidelines, a kidney biopsy is indicated in prospective living kidney donors with persistent microscopic hematuria and negative urological work-up. We investigated whether persistent microscopic hematuria at donor screening is associated with changes in post-donation eGFR, proteinuria, or blood pressure. METHOD: We included 701 living kidney donors who underwent two urinalyses before donation and had annual evaluation of estimated glomerular filtration rate (eGFR), protein:creatinine ratio (PCR) and systolic blood pressure (SBP). The association between pre-donation persistent microscopic hematuria (≥ 1 red blood cell per high power field or ≥3 red blood cell per µL) and outcomes was assessed using generalized linear mixed models. RESULTS: Mean age was 52 ± 11 years, median [interquartile range] follow-up time was 5 [2–8] years. Pre-donation persistent microscopic hematuria was present in 88 donors (80% female, versus 45% in non-hematuria group, P < 0.001). There were no significant associations between persistent microscopic hematuria at screening and course of eGFR [0.44 mL/min/1.73 m 2 increase/year for hematuria donors versus 0.34 mL/min/1.73 m 2 increase/year for non-hematuria donors (P = 0.65)], PCR (0.02 versus 0.04 mg/mmol increase/year, P = 0.38), or SBP (1.42 versus 0.92 mmHg increase/year, P = 0.17) post-donation, even after adjusting for pre-donation age, sex, body mass index, eGFR, PCR, SBP and ACE inhibitor/angiotensin receptor blocker use. Sensitivity analyses in subgroups with risk-factor(s) of kidney disease and subgroups with poorer post-donation courses of the outcomes yielded similar results. CONCLUSION: Donors with persistent microscopic hematuria at donor screening had no increased risk of progressive eGFR decline, proteinuria, or hypertension. Despite the limitation of potential selection bias, it seems safe to allow donors with persistent microscopic hematuria without other risk factors to donate without prior kidney biopsy. However, these results warrant validation on the longer term after donation.